A INCREASING EARLY DETECTION ABILITY OF NASOPHARYNGEAL CARCINOMA FOR DOCTOR IN MADIUN - Achmad Chusnu Romdhoni (Universitas Airlangga, 2023)
Increasing incidence of advanced nasopharyngeal carcinoma can reduce life expectancy. So that early detection and prevention of nasopharyngeal risk factors are needed to the community. Knowledge about nasopharyngeal carcinoma can increase public awareness to undergo early examination and treatment. The purpose of this activity is to increase knowledge and skills for doctors in early detection of nasopharyngeal carcinoma in the Madiun Raya area. Educational activities are carried out through seminars and training with lecture, discussion, practice methods, as well as pre-test and post-test. The results of the pre-test and post-test of seminar and training activities showed that there was a statistically significant difference (p < 0.0001). It is hoped that this seminar and training will be able to increase nasopharyngeal awareness in the community and be able to make a positive contribution to efforts to treat nasopharyngeal carcinoma in the wider community.